A TAXONOMIC REVISION OF BEGONIA VEITCHII (BEGONIACEAE). (26th March 2020) - Tebbitt, M. C.; Reynel, C.; Limachi, L. Huaylla; Martín, C. M.
Abstract : A taxonomic revision of Begonia veitchii Hook.f. is presented. Two taxa are newly recognised as synonyms of Begonia veitchii : B. baumannii Lemoine and B. clarkei Hook.f. Addditionally, two infraspecific taxa are newly described and illustrated: Begonia veitchii var. machupicchuensis Tebbitt, which is endemic to the Cusco Department of Peru, and B. veitchii var. lanatifolia Tebbitt, which is endemic to Chuquisaca Department, Bolivia. Begonia veitchii, as well as four taxa recognised as synonyms of B. veitchii – B. baumannii, B. rosaeflora Hook.f., B. coriacea A.DC. and B. clarkei – are lectotypified. A key, descriptions, distribution map and illustrations are provided for all the recognised infraspecific taxa of Begonia veitchii .